SDG1 no poverty : making the dream a reality - Cichos, Katarzyna; Lange Salvia, Amanda (Concise guides to the United Nations sustainable development goals, 2018)
For many decades the international community has endeavoured to eliminate extreme poverty; however, it is estimated that around 800 million people still live below the international poverty line of $1.90 a day. This book looks this global problem and presents applicable solutions to show that we can eliminate poverty today and meet the challenge of the UN Sustainable Development Goal 1.The first part of the book discusses what poverty and development are and asks whether the right to development is an international commitment to eradicate poverty. The second part looks at the strategy of the Sustainable Development Goals, and the concept of happiness for all people in the world. It examines the proposition of SDG1, evaluates the first actions taken in this area, and presents the best practice of recent SDG implementation. The final part considers several proposals and presents suggestions on how to make global action more effective.Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.